2008
DOI: 10.1083/jcb.200711149
|View full text |Cite
|
Sign up to set email alerts
|

Spinophilin participates in information transfer at immunological synapses

Abstract: The adaptive immune response is initiated by the presentation of peptides bound to major histocompatibility complex molecules on dendritic cells (DCs) to antigen-specific T lymphocytes at a junction termed the immunological synapse. Although much attention has been paid to cytoplasmic events on the T cell side of the synapse, little is known concerning events on the DC side. We have sought signal transduction components of the neuronal synapse that were also expressed by DCs. One such protein is spinophilin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Samd14 and Ppp1r9b have similar expression patterns during hematopoiesis (Lara-Astiaso et al, 2014) (Figure S2A) and in fetal erythroid precursors (Chen and Lodish, 2014) (Figure S2B). Immunostaining of expressed HA-Samd14 in G1E cells revealed a cytoplasmic localization (Figure 4B), resembling neurabin-2 in HeLa (Sagara et al, 2009) and immature dendritic cells (Bloom et al, 2008). ER-GATA-1 uniquely upregulated Samd14 expression in G1E-ER-GATA-1 cells (Figure S2C) (DeVilbiss et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…Samd14 and Ppp1r9b have similar expression patterns during hematopoiesis (Lara-Astiaso et al, 2014) (Figure S2A) and in fetal erythroid precursors (Chen and Lodish, 2014) (Figure S2B). Immunostaining of expressed HA-Samd14 in G1E cells revealed a cytoplasmic localization (Figure 4B), resembling neurabin-2 in HeLa (Sagara et al, 2009) and immature dendritic cells (Bloom et al, 2008). ER-GATA-1 uniquely upregulated Samd14 expression in G1E-ER-GATA-1 cells (Figure S2C) (DeVilbiss et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…In addition, previous studies have shown that the F-actin bundling protein spinophilin directly interacts with Dcx. To find out whether Dcx interacts with these actin-binding proteins, we cotransfected HEK293 cells with constructs expressing HA-Dcx and GFP-Arp3; GFP-α-actinin-1(Edlund et al, 2001); or spinophilin-GFP(Bloom et al, 2008). Results from immunoprecipitation and Western blotting indicate that Dcx interacts with spinophilin but not with Arp3 or α-actinin-1 (Figure 7C–7E).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we must recognize that the APC is contributing mechanical and functional contributions to IS surfaces. Recent studies have identified new roles for the APCs in modulating synapse structure and function (194, 195). We are careful to use the word amplification rather than artifact; the biology and signaling is the same, but we need to remind ourselves that the overall size/structure we see is tunable to the factors and constraints we introduce.…”
Section: Reconciling Differences Between In Vivo and In Vitro Systemsmentioning
confidence: 99%